Net ownership, utilization and malaria burden in the context of Piperonyl butoxide-LLINs intervention in western Kenya - Job Oyweri; Patrick O. Onyango; Maxwell G. Machani; Josephat Bungei; Sammy Cheruiyot; Yaw A. Afrane; Ming-Chieh Lee; Daibin Zhong; Guofa Zhou; John Githure; Harrysone Atieli; Guiyun Yan (PLoS ONE, 2025)
Background Pyrethroid-treated nets have reduced malaria in endemic areas, but insecticide resistance has hindered progress, prompting WHO to recommend piperonyl butoxide (PBO) based long-lasting insecticidal nets (LLINs). Kenya adopted PBO nets, but their usage is not well documented. This study aims to assess the uptake and effect of PBO nets versus pyrethroid-only LLINs (pyrethroid-LLINs) on malaria transmission in Western Kenya. Methods A cross-sectional study was conducted in Muhoroni Sub-County, Kisumu County, one year after net distribution between November and December 2023. Twelve villages were randomly selected, comprising 380 households and divided into two intervention arms of six villages. Group 1, with 181 households, received pyrethroid-LLIN, while Group 2, with 199 households, received PBO-LLINs. Data on net ownership and usage was collected using a standardized semi-structured questionnaire. Finger prick blood smears were collected on slides for microscopic examination, while dry blood spots (DBS) on filter paper were collected for real-time PCR (RT-PCR) diagnosis of Plasmodium infection in both intervention groups. Logistic regression was used to identify factors influencing net ownership and malaria prevalence, while a generalized linear model assessed factors affecting net usage. The χ² test was used to evaluate differences in demographic characteristics between the intervention arms. Results Overall, higher net ownership and usage was recorded in PBO-LLINs group compared to the pyrethroid-LLIN group after one year of net distribution. Among households, 89% in the pyrethroid-LLIN group and 96% in the PBO-LLIN group owned at least one net. Net usage was 80.2% in the pyrethroid-LLIN group and 87.6% in the PBO-LLIN group. Net attrition rate was 17.9% in pyrethroid-LLIN and 7.6% for PBO-LLIN group. Households with nets were 1.3 times more likely to use them [aOR=1.338 (95% CI = 1.224–1.462), p < 0.001). Bed ownership was 50.8% in the pyrethroid-LLIN group and 55.3% in the PBO-LLIN group. Not owning a bed decreased the likelihood of net usage by 13.3% [aOR=0.867 (95% CI = 0.816–0.920), p < 0.001]. Between the two groups, 75.7% of households in the pyrethroid-LLIN group and 66.8% in the PBO-LLIN group reported bedbug infestations in their homes. Bedbug infestation significantly affected net ownership (p = 0.018). Malaria parasite prevalence was 34.7% by qPCR in the pyrethroid-LLIN group and 29.0% in the PBO-LLIN group, with a prevalence ratio of 0.84 (95% CI: 0.65–1.03). Conclusion The study observed higher bednet ownership, usage, and lower malaria prevalence in the PBO-LLIN clusters compared to the pyrethroid-LLIN clusters. However, bedbug infestations and insufficient sleeping beds hindered net ownership and usage, limiting their overall effectiveness. These findings highlight the need for National Malaria Control Programs (NMCPs) to enhance community education on proper net use and maintenance through targeted initiatives, such as household visits and local workshops. Furthermore, incorporating bedbug control strategies and regular surveillance will improve compliance and net usage. Addressing these challenges will maximize the impact of PBO-LLINs and other next-generation nets, strengthening malaria control and elimination efforts in both urban and rural settings.